The seasons are changing - Ringström, Olle (2021)
The Swedish County of Västernorrland is facing the threat of the climate crisis and to create a resilient system against it regional and local policy implementation plays a key role. This thesis aimed to identify and analyse the discourses affecting Västernorrland adaptation progress and to understand the challenges facing the public officials responsible for policy implementation. To do this, the national climate change adaptation policy, regional action plan of Västernorrland, and transcribed interviews with Administrative County Board and municipality representatives in Västernorrland have been studied. Critical discourse analysis combined with field theory was used to identify the discursive and social practices affecting the narrative surrounding climate change adaptation in Västernorrland. The findings provide new insight into the challenges that are to be addressed if Västernorrland County is to reach sufficient adaptation action to become resilient against the expected climate change of the 21st century. Often heralded as a leading actor in climate change-related issues, Sweden’s government arrangement of adaptation policy implementation is limiting local and regional adaptation action. Although the existing networks and collaboratives efforts for adaptation action have the potential to successfully solve the problem, insufficient funds of the rural municipalities in the County and lack of mandate given to the County administrative board constrains the sustainable development of the County. Thus, the results suggest that additional funds available for municipalities to work with adaptation is needed for municipalities to prioritise adaptation and the County administrative board needs further mandate to work with implementing policy in Västernorrland if the County is to meet the national governments aim to reach Agenda 2030.